Resilient Infrastructure Public-Private Partnerships : Contracts and Procurement – The Case of Japan - World Bank (Washington, DC, 2018)
Resilient economic infrastructure plays an increasingly significant role in mitigating natural disaster risks, including hydrometeorological and geophysical hazards, especially in the contexts of climate variability and change. Building on the theoretical approaches to the key challenges in resilient infrastructure public-private partnerships (PPPs) outlined by Public-Private Infrastructure Advisory Facility (PPIAF), the World Bank's Global Infrastructure Facility (GIF) and the Tokyo Disaster Risk Management (DRM) Hub have initiated a knowledge project on "Resilient Infrastructure PPPs—Contracts and Procurement" to harness the knowledge and expertise gained from PPP projects in selected countries to help the governments of low- and middle-income countries to prepare and structure disaster-resilient infrastructure PPPs. This report presents a case study of infrastructure PPP projects in Japan under the knowledge development component. Japan is highly exposed to natural disaster risks ranging from earthquake, tsunami, cyclone, floods, and landslides to volcanic eruptions. Japan's experience in structuring resilient infrastructure PPPs offers policy recommendations and insights on how disaster and climate risks can be managed under PPPs.